Cropping Patterns in Mymensingh Region: Diversity, Constraint and Potential (Bangladesh Rice Journal, 2018)
A consistent and comprehensive database on cropping pattern, cropping intensity and crop diversity of a particular area is the prime importance for guiding policy makers, researchers, extentionists and development agencies for the future research and development planning. The study was carried out all the upazilas of Mymensingh region during 2015-16 using pre-designed and pre-tested semistructured questionnaire with a view to document the existing cropping pattern, crop diversity and cropping intensity. The most dominant cropping pattern Boro−Fallow−T. Aman occupied about onehalf of net cropped area (NCA) of the region distributed to 46 out of 47 upazilas. Single Boro cropping pattern ranked the second position which covered 23% of NCA distributed in 45 upazilas. A total of 129 cropping patterns were identified in the whole area of Mymensingh region under this investigation. The highest number of (30) cropping patterns were identified in Pakundia upazila of Kishoreganj and the lowest was (10) in Sreebardi of Sherpur. The lowest crop diversity index (CDI) was reported (0.111) in Mithamoin of Kishoreganj followed by 0.114 at Khaliajuri in Netrokona. The highest value of CDI was observed 0.933 at Dewanganj in Jamalpur followed by 0.920 at Bhairab in Kishoreganj. The range of cropping intensity values was recorded 101-249%. The maximum value was for Hossainpur and minimum for Itna and Mithamoin in Kishoreganj. At a glance the calculated CDI of Mymensingh region was 0.840 and the average cropping intensity was 187%.Bangladesh Rice j. 2017, 21(2): 217-235